Pengaruh Gaya Kepemimpinan, Kerjasama Tim Dan Komunikasi Terhadap Kinerja Karyawan PT. Bank XYZ (Persero) Tbk. - Saputra, Rio Adi; Pardiman, Pardiman; Amin, Muhammad Sirojuddin (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the influence of leadership style, teamwork, and communication on employee performance at PT. Bank XYZ (Persero) Tbk. The research background is based on the importance of improving employee performance to support organizational productivity and success, particularly in the highly competitive banking sector. This research employed a quantitative method with an associative approach. Data were collected through questionnaires distributed to 69 respondents who are employees of PT. Bank XYZ (Persero) Tbk., and then analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results show that leadership style, teamwork, and communication partially have a positive and significant effect on employee performance. These findings indicate that effective leadership, strong teamwork support, and open and clear communication can enhance employee performance. In conclusion, the company needs to continuously optimize leadership practices, foster a strong teamwork culture, and strengthen communication patterns to further improve employee performance. Keywords: Leadership Style, Teamwork, Communication, Employee Performance